2021
DOI: 10.3389/frai.2021.630955
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of the Receptor Binding Domain of SARS-CoV-2 Spike Protein and Prediction of a B-Cell Antigenic Epitope Using Structural Data

Abstract: COVID-19, the illness caused by the SARS-CoV-2 virus, is now a worldwide pandemic with mortality in hundreds of thousands as infections continue to increase. Containing the spread of this viral infection and decreasing the mortality rate is a major challenge. Identifying appropriate antigenic epitopes from the viral proteins is a very important task for vaccine production and the development of diagnostic kits and antibody therapy. A novel antigenic epitope would be specific to the SARS-CoV-2 virus and can dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
15
0
5
Order By: Relevance
“…This structure binds to the host cell receptor, angiotensin-converting enzyme 2 (ACE2), allowing the virus to enter the cell. In addition, RBD includes a receptor-binding motif (RBM), which contains amino acid residues that directly contact ACE2 [30,31]. The S2 subunit includes the fusion peptide (FP), 2 heptad repeat (HR1 and HR2) subdomains, a transmembrane helix, and a cytoplasmic tail.…”
Section: Virological Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…This structure binds to the host cell receptor, angiotensin-converting enzyme 2 (ACE2), allowing the virus to enter the cell. In addition, RBD includes a receptor-binding motif (RBM), which contains amino acid residues that directly contact ACE2 [30,31]. The S2 subunit includes the fusion peptide (FP), 2 heptad repeat (HR1 and HR2) subdomains, a transmembrane helix, and a cytoplasmic tail.…”
Section: Virological Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…Therefore, considering the key observation of the global increase in hydrophobicity across the selected substitutions, we asked what these mutations could bring on a structural level. We constructed 475 structural models of S protein corresponding to all 148 substitutions in 4 known conformational states which are involved in the recognition, namely unbound (“closed” 66 , 67 ( N =148), “open” 66 , 67 ( N =148)), bound [68] ( N =148) and postfusion [39] ( N =31) ( Figure1 (a-d) ). As a control, the Wuhan strain S protein was included.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was found that viral epitopes (such as Influenza and CMV) that lack sequence identity with SARS2 are able to stimulate an immune response (Mahajan et al, 2021) which we believe is attributable to similar protein structural formation. In this regard, we postulate that high VOC S1-CTD and S1-NTD structural similarity (TM > 0.70) with either the original SARS2 or endemic HCoV could putatively have crossreactivity with the original SARS2 and endemic HCoV spike models (Ladner et al, 2021) possibly ascribable to having multiple similar conformational epitopes that are considered valuable in neutralizing viral pathogenesis (Khare et al, 2021). This is consistent with previous work showing that T cell frequencies against the original SARS2 have likewise been correlated to VOC (Stankov et al, 2021) which we suspect to be due to structural similarity (particularly S1-CTD).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VOC have been shown to partially escape humoral immune response, however, VOC are found to be unable to escape cellular immune response among convalescent donors and vaccinees (Geers et al, 2021). This would highlight the putative significance of cellular immune response [particularly Th1 and Tfh cells (Poland et al, 2020) ] in providing lasting protection against VOC and, more importantly, the T cell-recognizing conformational epitopes that can counteract viral infectivity (Khare et al, 2021).…”
Section: Discussionmentioning
confidence: 99%